PENDAMPINGAN PRODUKSI PAVING BLOCK: SOLUSI BERKELANJUTAN UNTUK PENGELOLAAN SAMPAH PLASTIK DI DESA DABUAN, KECAMATAN TLANAKAN, KABUPATEN PAMEKASAN - Khoiri, Moh. Miftahol; Izuddin, Muhammad; Shaleh, Badrus; Muktirrahman, Muktirrahman; Maksum, Maksum (Abdimas IAI Ngawi, 2025)
The plastic waste problem in Dabuan Village is caused by a lack of public awareness and the lack of an effective management system, so an innovative and sustainable solution is needed. This service aims to provide alternative waste management through the production of recycle-based paving blocks with the KUPAR cycle approach (To Know, To Understand, To Plan, To Action, To Reflection). The methods used include observation, interviews, focus group discussion (FGD), technical training, and evaluation and monitoring. The results of the service showed that the community experienced an increase in skills in sorting, chopping, mixing, and molding plastic-based paving blocks, and some groups began to produce paving blocks independently. The implications of this activity not only reduce plastic waste but also open up economic opportunities for the community through the production and marketing of paving blocks. The sustainability of this program requires support from the village government as well as collaboration with various stakeholders so that this recycling innovation can develop into a sustainable environmental and economic solution. Keywords: plastic waste, paving blocks, recycling, community empowerment   Abstrak: Permasalahan sampah plastik di Desa Dabuan disebabkan oleh kurangnya kesadaran masyarakat dan minimnya sistem pengelolaan yang efektif, sehingga diperlukan solusi inovatif dan berkelanjutan. Pengabdian ini bertujuan untuk memberikan alternatif pengelolaan sampah melalui produksi paving block berbasis daur ulang dengan pendekatan siklus KUPAR (To Know, To Understand, To Plan, To Action, To Reflection). Metode yang digunakan mencakup observasi, wawancara, Focus Group Discussion (FGD), pelatihan teknis, serta evaluasi dan monitoring. Hasil pengabdian menunjukkan bahwa masyarakat mengalami peningkatan keterampilan dalam memilah, mencacah, mencampur, dan mencetak paving block berbahan dasar plastik, serta beberapa kelompok mulai memproduksi paving block secara mandiri. Implikasi dari kegiatan ini tidak hanya mengurangi limbah plastik, tetapi juga membuka peluang ekonomi bagi masyarakat melalui produksi dan pemasaran paving block. Keberlanjutan program ini memerlukan dukungan dari pemerintah desa serta kolaborasi dengan berbagai pemangku kepentingan agar inovasi daur ulang ini dapat berkembang menjadi solusi lingkungan dan ekonomi yang berkelanjutan. Kata Kunci: sampah plastik, paving block, daur ulang, pemberdayaan masyarakat